2014
DOI: 10.1007/s11664-014-3420-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nanopores on the Tensile/Compressive Mechanical Behavior of Crystalline CoSb3: A Molecular Dynamics Study

Abstract: Recently, many experimental studies have reported that inserting nanopores into thermoelectric materials can both remarkably reduce the thermal conductivity and significantly improve the thermoelectric performance of the target material. Research on nanoporous materials has thus been attracting much attention worldwide. However, most of the studies mainly focus on the preparation of nanoporous material and the effect of different geometrical sizes of nanopores on thermal conductivity and thermoelectric propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Because of its importance for engineering applications, the mechanical properties of CoSb 3 have been examined recently. Rogl and Rogl reported experimental mechanical properties of doped skutterudite CoSb 3 such as elastic moduli, fracture toughness, and failure stress . They showed that CoSb 3 has mechanical properties competitive with other TE materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its importance for engineering applications, the mechanical properties of CoSb 3 have been examined recently. Rogl and Rogl reported experimental mechanical properties of doped skutterudite CoSb 3 such as elastic moduli, fracture toughness, and failure stress . They showed that CoSb 3 has mechanical properties competitive with other TE materials.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al used molecular dynamics simulations (Force field) to examine the stress–strain relationships of CoSb 3 and found it to be a typical brittle material . Li et al studied the tensile/compressive mechanical behavior of nanoporous skutterudite CoSb 3 thermoelectric material using molecular dynamics and found that elastic modulus of single crystalline CoSb 3 decreased with the increasing porosity. , However, the mechanism for brittle failure and the intrinsic mechanical properties of CoSb 3 remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For calculating the per-atom stress, initially the stresses of all the atoms of the system were added together. The computed quantity was in units of pressure × volume (Li et al 2015), and the volume over which the stress is averaged (simulation box volume) was considered to be the characteristic volume. Hence, the total stress was divided by system volume to obtain the stress per atom (Li et al 2015) (Fig.…”
Section: Simulation Procedures and Resultsmentioning
confidence: 99%